Cardioneuroablation: a new era for vagal syncope? - Lima Lopes, Joana (2024)
42 years old male athlete Bradycardia and vagal syncope episodes ECGs showed sinus rhythm with bradycardia (40-44 bpm) Transthoracic Echocardiogram: normal TILT test: positive - 2b cardio inhibitory response and 20s asystole